2008
DOI: 10.1007/s12149-008-0166-8
|View full text |Cite
|
Sign up to set email alerts
|

Static and moving phantom studies for radiation treatment planning in a positron emission tomography and computed tomography (PET/CT) system

Abstract: When a threshold value of 35% of the measured maximum (18)FDG activity was adopted, the sizes of PET delineation were almost the same for static and moving phantom spheres of 22 mm or more in the axial plane. In addition, PET images have the potential to provide an individualized ITV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 39 publications
2
37
0
Order By: Relevance
“…We also determined the tumor volumes of true-positive lesions using an automated attenuation-corrected FDG PET method according to a previous study [12]. ROIs placed over true-positive lesions were drawn manually referring to fusion images or CT images.…”
Section: Discussionmentioning
confidence: 99%
“…We also determined the tumor volumes of true-positive lesions using an automated attenuation-corrected FDG PET method according to a previous study [12]. ROIs placed over true-positive lesions were drawn manually referring to fusion images or CT images.…”
Section: Discussionmentioning
confidence: 99%
“…N Two absolute threshold PET contours were delineated using an absolute standardised uptake value (SUV) threshold of 2.5 (GTV SUV2.5 ) and a threshold of 35% (GTV 35%SUVMAX ) of the maximal SUV within the target image (SUV MAX ) [16,17].…”
Section: Target Volume Delineationmentioning
confidence: 99%
“…Hence the PET component of the scan contains an element of the respiratory motion of a lung tumour. It has been suggested that this four-dimensional (4D) element of a PET scan might be able to define an internal target volume, compensating for all respiratory motion [16,23]. Thus, with current scanning protocols, a 3D scanning modality (CT) is in effect being combined with a 4D scanning modality (PET).…”
Section: Target Volume Delineationmentioning
confidence: 99%
“…Okubo et al [31] constructed an elliptic phantom and found that when a threshold value of 35% of the measured maximum 18 FDG activity was adopted, the sizes of PET delineation were almost the same for static and moving phantom spheres of 22 mm or more in the axial plane.…”
Section: Thresholding Methods For Target Outliningmentioning
confidence: 99%
“…An annular ring of water bags of 3 cm thickness was fitted over an International Electro-technical Commission (IEC) phantom in order to obtain counting rates similar to those found in average patients. They found that both the target size and the T/B ratio play a major role in explaining the variance of the percentage threshold throughout the whole range of target sizes and T/B ratios examined.Okubo et al [31] constructed an elliptic phantom and found that when a threshold value of 35% of the measured maximum 18 FDG activity was adopted, the sizes of PET delineation were almost the same for static and moving phantom spheres of 22 mm or more in the axial plane.Adaptive thresholding methods: Black et al [13] proposed an advanced adaptive threshold method for target delineation using PET images in which threshold value varies with the size of the target. However, they employed SUV, which does not represent the quantity of choice for the radiation treatment planning segmentation as mentioned previously [14].…”
mentioning
confidence: 99%